Beyond earnings : applying the HOLT CFROI and economic profit framework - Holland, David A., 1961-; Matthews, Bryant A., 1966- (Wiley, 2017)
"Step up stock selection with advanced valuation techniques Beyond Earnings provides finance professionals with the most advanced techniques available for complex valuation and corporate performance analysis. Deep in detail and comprehensive in scope, this book features the first empirical discussion of mean-reversion in corporate profitability and growth, with expert guidance toward practical solutions. By focusing on cash flow and the economics of a companys performance, the discussion relates a more effective process for stock screening, selection, and valuation. Step-by-step calculations guide you through the application of the HOLT CFROI and Economic Profit approaches for measuring operating performance, and expert insight from Credit Suisse researchers and consultants sheds new light on familiar situations. Stock selection is the critical point in the performance matrix, and screening and valuation practices weigh heavily into a firms performance. As investors face increasing pressure to perform at ever-higher levels, this book provides essential analysis methods that help paint a more complete picture of a potential investments performance. Assess a firms performance accurately by adjusting for accounting distortions Calculate economic profit and CFROI Estimate future cash flow, profit streams, and the firm's value Model terminal value and eliminate the perpetuity assumption The effort to outperform benchmarks and exchange-traded funds grows increasingly Sisyphean as professional investors face mounting pressure from all sides. When the market is not performing to the level required to attain strategic goals, smarter stock selection becomes the lynchpin of high-performing firms. Advanced modeling provides an edge over traditional models in that it paints a truer picture of a corporations status, and extends that vision further into the future to facilitate more educated decision-making. Beyond Earnings is the professional manual to enhanced stock analysis and valuation, with invaluable guidance you won't find anywhere else."--